2004
DOI: 10.1093/ndt/gfh124
|View full text |Cite
|
Sign up to set email alerts
|

Acute arterio-venous fistula occlusion decreases sympathetic activity and improves baroreflex control in kidney transplanted patients

Abstract: Arterial baroreceptor activation and increased arterial baroreflex sensitivity decrease heart rate during AVF occlusion. In addition, our study is the first to demonstrate that arterial baroreflex activation decreases sympathetic nerve traffic during the Nicoladoni-Branham sign.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 14 publications
0
18
0
Order By: Relevance
“…Fistula flow was estimated through the decrease in CO produced by compression of the AVF. Indeed, previous observations have shown that this decrease correlates with fistula flow (14), and this parameter has been used as a substitute for direct fistula flow measurement (6,15,16). The AVF was occluded at the end of the initial echocardiographic study by inflating a sphygmomanometer cuff to a 50 mmHg suprasystolic pressure for 30 s (6).…”
Section: Methodsmentioning
confidence: 99%
“…Fistula flow was estimated through the decrease in CO produced by compression of the AVF. Indeed, previous observations have shown that this decrease correlates with fistula flow (14), and this parameter has been used as a substitute for direct fistula flow measurement (6,15,16). The AVF was occluded at the end of the initial echocardiographic study by inflating a sphygmomanometer cuff to a 50 mmHg suprasystolic pressure for 30 s (6).…”
Section: Methodsmentioning
confidence: 99%
“…The hemodynamic significance of an AVF could be determined by studying the hemodynamic differences induced by acute AVF occlusion [15]. Therefore, we decided to evaluate the changes in hemodynamic and microcirculatory blood flow after acute occlusion of the fistula.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we decided to evaluate the changes in hemodynamic and microcirculatory blood flow after acute occlusion of the fistula. In humans with an AVF, the hemodynamic dif ferences after temporary compression of the fistula are called the Nicoladoni or Branham sign, which consists of a decrease in HR, an increase in blood pressure, and a reduction in pulse pressure [2, 15]. In the current study, SBP and DBP increased significantly after acute occlusion of the fistula; some hemodynamic mechanisms might contribute to these effects, such as a sudden increase in systemic vascular resistance and a decrease in cardiac venous return after occlusion of the AVF [15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In small physiologic studies, acute occlusion of stable AV fistulas used for HD increased baroreceptor sensitivity to a greater degree than did carotid sinus massage 5 . Further vagal-mediated bradycardia from AV fistula occlusion may also be mitigated with atropine 3 or possibly with increased venous return achieved by lifting the lower extremities when the subject is in a supine position.…”
Section: Discussionmentioning
confidence: 99%